DDEL-19. TREATMENT ADHERENCE OF SELUMETINIB AMONG PATIENTS DIAGNOSED WITH NEUROFIBROMATOSIS TYPE I AND PLEXIFORM NEUROFIBROMA IN THE UNITED STATES. (14th November 2022) - Yang, Xiaoqin; Gao, Chi; Ahsan, Sama; Dettling, Theresa; Gu, Yuqian; Banatwala, Azeem; Cheng, Wendy
Abstract: INTRODUCTION: Selumetinib is the only FDA-approved (April 2020) treatment for pediatric patients with neurofibromatosis type 1 (NF1) and symptomatic inoperable plexiform neurofibroma (PN). Real-world information on selumetinib treatment patterns is lacking. Our study assessed treatment adherence among pediatric patients prescribed selumetinib using a large health claims database. METHODS: Eligible patients aged 2-21 years with ≥ 1 selumetinib prescription fill in 4/2019-1/2022 (1st fill defines index date), ≥ 6 months of eligibility pre index (baseline), ≥ 3 months of eligibility post index (observation period) and no clinical trial participation were identified from the Clarivate® DRG® Real World Data Repository. Baseline patient characteristics were summarized. Adherence to selumetinib during observation period was evaluated using medication possession ratio (MPR) among patients with ≥ 2 prescription fills and proportion of days covered (PDC) over fixed time periods. Proportion of adherent patients (≥ 80% MPR or PDC) were reported. RESULTS: 73 eligible patients were identified with mean age of 13.0 (standard deviation [SD]: 4.7) years, 54.8% male, 65.8% with commercial insurance, and 31.5% with Medicaid. The most common baseline treatment was pain medication (23.3%). The mean (SD) Quan Charlson Comorbidity Index was 0.9 (1.3) and the most common NF1 PN-related comorbidities were attention-deficit hyperactivity disorder (11.0%) and headaches (6.8%). The mean (SD) MPR was 86.0% (19.8%) and 71.2% of patients were adherent (MPR ≥ 80%). At 60, 90 and 120 days, the mean PDC was 79.6%, 73.0% and 68.4%, respectively; and the proportion of adherent patients (PDC ≥ 80%) was 56.2%, 56.2% and 48.6%, respectively. Analyses assessing PDC at 150 and 180 days indicated slightly under half of patients remained adherent. CONCLUSION: Mean adherence to selumetinib was high; about half to three-quarters of NF1 PN pediatric patients were adherent to selumetinib–a clinically important finding given the generally low medication adherence rates in pediatric patients.